EFEKTIVITAS PELAKSANAAN PENDIDIKAN DAN PELATIHAN KEPEMIMPINAN (DIKLATPIM) IV PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA APARATUR (BKPSDMA) KABUPATEN SINJAI - Nursaifullah; Zulkifli Arifin (Program Studi Administrasi Publik, 2019)
The purpose of this study was to determine the effectiveness of the Implementation of Leadership Education and Training (DIKLATPIM) IV at the Personnel Development and Human Resources Development Agency (BKPSDMA) Sinjai Regency. This type ofresearch is qualitative, data collection techniques namely observation, interviews and documentation. The informant was the Chair of the Diklatpim IV Executive Committee, Widyaswara, an employee who had participated in the training for the past two years.Data analysis techniques by data reduction, data presentation and conclusions. Based on the results of the discussion of the research results, it is known that at the stage of diagnosing the need for organizational change, in this stage it has run well as evidenced by the participants being able to collect and manage information, identify alternatives and determine the best alternative choices because participants have been taught the conception of creative and innovative thinking in training activities . The commitment building stage, in this stage the participants are able to establishcooperation and cohesiveness within the organization and are able to implement appropriate disciplinary behavior promises of concern for the quality of the results of cooperation, honesty, and responsibility because they have been taught to build jointcommitment in training activities. The stage of designing change, in this stage the participant is able to compile an innovative project design change related to the activity of the tasks and functions of the organization because it has been taught the introduction of self potential and emotional intelligence in training activities. In the leadership laboratory stage, in this stage the participants were directed to implement the change project in accordance with the activities related to the tasks and functions of the unit involving the stake holders because they had been taught the leadership laboratory in the training activities. Evaluation phase, in this stage participants can present the project changes produced in accordance with the milestone accompanied by evidence in the form of notes / transcripts written / audio / visual, photos, attendance lists and so on because participants have been guided in training activities. The results of the study concluded that the Implementation of Leadership Education and Training (DIKLATPIM) IV at the Personnel Development and Human Resources Development Agency (BKPSDMA) Sinjai District had been running effectively.